Strengthening integrated sexual reproductive health and rights and HIV services programs to achieve sustainable development goals 3 and 5 in Africa - Rose-Mary Asong Tazinya; Julia Marie Hajjar; Sanni Yaya (BMC, 2022)
Abstract Each year, over 200 million women globally cannot prevent pregnancy through modern contraceptive methods, with 70-80% of these women residing in sub-Saharan Africa. Consequently, almost 50% of pregnancies are unintended and 35 million unsafe abortions occur annually in the region. Further, sub-Saharan Africa has the highest burden globally of Human Immune-Deficiency Virus (HIV) infection, and over 57% of those affected are women. Women with a positive HIV status in sub-Saharan Africa experience higher rates of unintended pregnancy and unsafe abortion practices. In this commentary, we propose strategies to strengthen integrated sexual and reproductive health and rights (SRHR) and HIV services programs to improve the sexual and reproductive health of girls and women and to work towards achieving SDGs 3 and 5 in sub-Saharan Africa. We suggest a focus on capacity building, strengthening intersectoral collaborations, and improving governance and financial investment.